2018
DOI: 10.25301/jpda.274.172
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Awareness Among Medical & Dental Students of Bahria University Medical and Dental College

Abstract: Pakistan has a high rate of incidence of oral cancer. In Pakistan, betel nut, betel quid and tobacco are found to be the most important causative agents of oral cancer. Timely detection and diagnosis of oral cancers can improve their responsive to treatments, consequently decreasing mortality rate and increasing the prognosis rate. The objective of this study was to report the knowledge and information about the different causes, risk factors and clinical appearance of oral cancer among undergraduate dental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The majority of oral cancers-about 90%-are squamous cell carcinomas (8) (9). Oral cancer, with its highly unpredictable morbidity rate, is one of the most common malignancies affecting the general population of Pakistan today (10). In most ethnic groups, men are two to three times more likely than women to get oral cancer (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of oral cancers-about 90%-are squamous cell carcinomas (8) (9). Oral cancer, with its highly unpredictable morbidity rate, is one of the most common malignancies affecting the general population of Pakistan today (10). In most ethnic groups, men are two to three times more likely than women to get oral cancer (1).…”
Section: Introductionmentioning
confidence: 99%
“…About 200,000 deaths occur due to oral cancer annually worldwide (12). Oral and lip cancer accounts for 8.6 per cent of all new cancer cases in Pakistan and is responsible for 7.2 per cent of all cancer deaths in Pakistan (10). The results, released by Shaukat Khanam Cancer Hospital in Lahore, showed that oral cancer is the third most common cancer in Pakistani women after breast and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation